Tata Kelola Monkey Forest Sebagai Sumber Daya Milik Bersama dalam Kajian The Commons di Desa Adat Padangtegal - Prayoga, Galih; Erawan, I Ketut Putra; Pramana, Gede Indra (Jurnal Nawala Politika, 2023)
This research try to see the Monkey Forest tourist destination as a source of livelihood for indigenous peoples. Using the commons theory by Elinor Ostrom and the commons concept by Michael Cox, this study looks at the background of traditional institutions that have resources and are managed independently according to customary conditions. This research reveals the steps of the traditional village in protecting the Monkey Forest under the responsibility of the Padangtegal Traditional Village through policies and actors who have the power to mobilize indigenous peoples. Researchers indicated that there was intervention from external parties from the traditional village in the process of developing the Monkey Forest because of the strategic location of the area in the center of Ubud District which is a well-known tourism area in Bali and even worldwide. Efforts to develop the Monkey Forest will be seen historically regarding the participation of the community and traditional institutions in preserving the Monkey Forest so that it becomes one of the best tourist destinations in the Province of Bali.   Keywords: Traditional Village, The Commons Theory, Monkey Forest, Padangtegal Traditional Vilage.